PELAKSANAAN PERJANJIAN KREDIT DENGAN JAMINAN FIDUSIA PADA KOPERASI SWAMITRA DI PEKANBARU - Tengku Sundari Pratiwi; Maryati Bachtiar; Dasrol ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Cooperative is a social economic organization of the people, in the form of a cooperative legal entity that is not a concentration of capital. Membership of cooperatives is based on voluntary interests, rights and duties. One form of cooperatives is a savings and credit cooperatives that help members in the field of credit. Whereas the availability of capital derived from members is relatively insufficient. So that the cooperative needs assistance through Swamitra pattern, which is a form of cooperation or partnership with Bank Bukopin to develop, as well as modernize cooperative savings and loan business to improve cooperative performance and increase cooperative capital to be more developed.The main problem in this research is how the implementation of credit agreement with fiduciary guarantee on Koperasi Swamitra in Pekanbaru and form of settlement of wanprestasi problem that happened in the implementation of credit agreement with fiduciary guarantee at Swamitra Cooperative in Pekanbaru.The research method that writer use is, observational research by way of survey that writer do direct research to research location that is in Koperasi Swamita Pekanbaru, while the nature of this research is descriptive that this research give clearer picture and detail about implementation of credit agreement with fiduciary guarantee at Swamitra Cooperative in Pekanbaru.The result of this research is that in the implementation of credit agreement with fiduciary guarantee at Swamitra Cooperative in Pekanbaru not fully run in accordance with agreed agreement between the borrower of fund (debtor), with the Swamitra Cooperative as the creditor. This is due to the existence of customers who default in credit agreement on Koperasi Swamitra. So that the existence of wanprestasi made by the customer, an obstacle in the implementation of the credit agreement. Settlement of wanprestasi made by creditors is to provide a warning to the debtor and prioritize the settlement by deliberation between the creditor and the debtor without causing the other party. The point is to solve jointly between the cooperative party as a creditor with its members as the debtor, with deliberations seeking the best way out.Keywords: Agreement, Debitor, Creditor, Implementation, Fiduciary